Efficient recovery of rare earth elements from coal based resources: a bioleaching approach. (June 2020) - Sarswat, P.K.; Leake, M.; Allen, L.; Free, M.L.; Hu, X.; Kim, D.; Noble, A.; Luttrell, G.H.
Abstract: Rare earth element (REE) resources in coal-related materials are vast. Assuming a coal production rate of 600 million short tons per year with an average REE content of 200 ppm, the potential REE resource is 120, 000 tons per year, which is similar to the annual global production of REEs. Most of those resources that are associated with coal-related materials are found in association with the gangue or ash-based content from the coal ore. Under normal coal plant operation, the REEs often end up in refuse piles or tailings impoundments. In many cases, these REEs can be recovered at low cost using appropriate coal preparation, heap leaching, solvent extraction and/or selective precipitation, followed by subsequent separation and purification of individual REEs. In the present research, the processing approach uses a natural pyrite stream, which was removed during coal cleaning and used to enhance leaching. Bio-oxidation has been used commercially to accelerate leaching, and this approach has been applied to coal-based materials. The ferric ions generated from bio-oxidation oxidize sulfide minerals such as pyrite, which generates acid. Both acid and ferric ions are helpful for leaching REEs, as well as for removing residual sulfides, thereby preventing future acid mine drainage and related liabilities. It can be seen that, recovery of REEs from coal waste materials can enable coal producers to use untapped REEs resources to produce revenue and extend resource life while simultaneously reducing future environmental issues and costs. Highlights: A methodology to recover rare earth elements (REEs) from coal-waste materials was investigated. Bioleaching approach was used to leach the coal refuse material. Solvent extraction and precipitation steps were also performed to selectively recover REEs.